Magnetic Resonance-Guided High-Intensity Focused Ultrasound (MR-HIFU): Technical Background and Overview of Current Clinical Applications (Part 1) - Siedek, Florian; Yeo, Sin Yuin; Heijman, Edwin; Grinstein, Olga; Bratke, Grischa; Heneweer, Carola; Puesken, Michael; Persigehl, Thorsten; Maintz, David; Grüll, Holger (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Background Extracorporeal high-intensity focused ultrasound (HIFU) is a promising method for the noninvasive thermal ablation of benign and malignant tissue. Current HIFU treatments are performed under ultrasound (US-HIFU) or magnetic resonance (MR-HIFU) image guidance offering integrated therapy planning, real-time control (spatial and temperature guidance) and evaluation.Methods This review is based on publications in peer-reviewed journals addressing thermal ablation using HIFU and includes our own clinical results as well. The technical background of HIFU is explained with an emphasis on MR-HIFU applications. A brief overview of the most commonly performed CE-approved clinical applications for MR-HIFU is given.Results Over the last decade, several HIFU-based applications have received clinical approval in various countries. In particular, MR-HIFU is now approved for the clinical treatment of uterine fibroids, palliation of bone pain, ablation of the prostate and treatment of essential tremor as a first neurological application.Conclusion MR-HIFU is a patient-friendly noninvasive method for thermal ablation which has received clinical approval for several applications. Overall, clinical data demonstrate treatment efficacy, safety and cost efficiency.Key Points: Citation Format
Keywords: HIIFU; interventional procedures; ablation procedures; hyperthermia; uterine fibroids; pain palliation